Relación Entre Inteligencia Emocional Y Conducta En Adolescentes De 12 Y 13 Años En Una Institución Educativa De Tuluá (2023)
The objective of this study is to analyze the relationship between Emotional Intelligence and behavior. For this, there was the participation of 63 students between 12 and 13 years of age, from the seventh grade of secondary school at the Julia Restrepo Educational Institution, Santa Clara headquarters located in the city of Tuluá.